EFFECT OF PERIOPERATIVE DEXMEDETOMIDINE ON CARDIAC SURGERY OUTCOME - ZAFAR, H; ASHRAF, T; AHMED, N (Biological and Clinical Sciences Research Journal, 2022)
This retrospective study was designed to assess the impact of perioperative dexmedetomidine on the outcome of open-heart surgery. This study was conducted at the Faisalabad Institute of Cardiology Faisalabad from 01 Jan 2022 to Dec 2022. A total of 350 fulfilled the inclusion criteria and were included in the study. Informed consent of the participants was taken. The ethical board of the hospital approved the study. Subjects were divided into the dexmedetomidine group (who were administered dexmedetomidine peri operatively, 179 (51%)) and non-dexmedetomidine group (who were not helped dexmedetomidine peri operatively, 171(48.8%).0.24-0.6 μg/kg/h was infused intravenously after cardiopulmonary bypass. The was continued for more than twenty-four hours postoperatively.10 out of 350 subjects (2.8%) died in hospital, and 14 (4%) died within thirty days. Perioperative dexmedetomidine infusion resulted in a significant reduction in hospital and 30-day mortality. In-hospital mortality in the dexmedetomidine and non-dexmedetomidine group were 1.22% and 4.6%, respectively (P=.008). 30-day mortality in the dexmedetomidine and non-dexmedetomidine groups was 1.8% and 5.2%, respectively (P=.002). Perioperative dexmedetomidine significantly reduced post-operative sepsis (0.8% vs. 2.2%, P=.043) and other complications (46.19% vs. 56.07%, P=.0205). There was no difference in the duration of hospital stay, ICU stay, post-operative ventilation time, and incidence of delirium and MACEs. So, it can be concluded that perioperative intravenous dexmedetomidine results in improved hospital and thirty-day survival and is associated with a decrease in post-operative delirium and overall complications.